Dispersal ability predicts spatial genetic structure in native mammals persisting across an urbanization gradient - Jonathan L. Richardson; Sozos Michaelides; Matthew Combs; Mihajla Djan; Lianne Bisch; Kerry Barrett; Georgianna Silveira; Justin Butler; Than Thar Aye; Jason Munshi‐South; Michael DiMatteo; Charles Brown; et al. (Evolutionary Applications, 2021)
Abstract As the rate of urbanization continues to increase globally, a growing body of research is emerging that investigates how urbanization shapes the movement—and consequent gene flow—of species in cities. Of particular interest are native species that persist in cities, either as small relict populations or as larger populations of synanthropic species that thrive alongside humans in new urban environments. In this study, we used genomic sequence data (SNPs) and spatially explicit individual‐based analyses to directly compare the genetic structure and patterns of gene flow in two small mammals with different dispersal abilities that occupy the same urbanized landscape to evaluate how mobility impacts genetic connectivity. We collected 215 white‐footed mice (Peromyscus leucopus) and 380 big brown bats (Eptesicus fuscus) across an urban‐to‐rural gradient within the Providence, Rhode Island (U.S.A.) metropolitan area (population =1,600,000 people). We found that mice and bats exhibit clear differences in their spatial genetic structure that are consistent with their dispersal abilities, with urbanization having a stronger effect on Peromyscus mice. There were sharp breaks in the genetic structure of mice within the Providence urban core, as well as reduced rates of migration and an increase in inbreeding with more urbanization. In contrast, bats showed very weak genetic structuring across the entire study area, suggesting a near‐panmictic gene pool likely due to the ability to disperse by flight. Genetic diversity remained stable for both species across the study region. Mice also exhibited a stronger reduction in gene flow between island and mainland populations than bats. This study represents one of the first to directly compare multiple species within the same urban‐to‐rural landscape gradient, an important gap to fill for urban ecology and evolution. Moreover, here we document the impacts of dispersal capacity on connectivity for native species that have persisted as the urban landscape matrix expands.